Global map of the gravity anomaly corrected for complete effects of the topography, and of density contrasts of global ocean, ice, and sediments - TENZER, Robert; HAMAYUN; VAJDA, Peter (Contributions to Geophysics and Geodesy, 2021)
We compile a global map of the sediments and ice density contrast stripped topographically and bathymetrically corrected gravity anomalies using the spherical harmonic representation of the gravity field. The complete topographic effect to the gravity anomaly comprises the direct topographic effect and the secondary indirect topographic effect. Gravitational effects of the density contrasts of three considered global structural crustal elements – oceans, sediments, and ice – are removed (stripped) from the topographically corrected gravity anomaly. The complete effects of these density contrasts also consist of the direct and the secondary indirect effects. In this study, we model globally the complete effects of the topography and of density contrasts (relative to average crustal density) of major anomalous geological structures inside the Earth’s crust due to ocean, ice, and (marine and continental) sediments. The gravity anomalies are computed from the coefficients of a global geopotential model (GGM) with a spectral resolution complete to degree 180. The same spectral resolution is used to compute the complete effects to the gravity anomaly due to the topography and bathymetry. The coefficients of a global elevation model (GEM) are used to compute the complete topographical effect, adopting the average crustal density 2670 kg/m3. The coefficients of a global bathymetric (ocean-depth) model (GBM) are used to compute the complete bathymetric (ocean density contrast) effect,adopting the mean ocean saltwater density 1030 kg/m3. The coefficients of a global ice thickness model (GITM) generated from the 2×2 arc-deg geographical grid of ice thickness data are used to compute the complete ice density contrast effect with a spectral resolution complete to degree 90, adopting the mean ice density 913 kg/m3. Finally, the global data of sediment thickness and density with the 2×2 arc-deg geographical resolution are used to compute the complete sediment mass density contrast effect.